2015
DOI: 10.4049/jimmunol.1501375
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced PTEN and PI3K Signaling Impairs Class Switch Recombination

Abstract: Class switch recombination (CSR) generates isotype-switched antibodies with distinct effector functions. B cells express phosphatase and tensin homolog (PTEN) and multiple isoforms of class IA phosphoinositide 3-kinase (PI3K) catalytic subunits, including p110α and p110δ, whose roles in CSR remain unknown or controversial. Here, we demonstrate a direct effect of PTEN on CSR signaling by acute deletion of Pten specifically in mature B cells, thereby excluding the developmental impact of Pten deletion. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
1
20
1
Order By: Relevance
“…CH12 lymphoma cells were cultured as described previously. 17 G1XP lymphomas were generated, established and cultured as described previously. 18 Ramos, OCI-LY1, OCI-LY3, OCI-LY7 and DHL-16 were gifts from Dr. Wing C. Chan (University of Nebraska, NE, USA) and were cultured in 10% fetal bovine serum lymphocyte medium.…”
Section: Methodsmentioning
confidence: 99%
“…CH12 lymphoma cells were cultured as described previously. 17 G1XP lymphomas were generated, established and cultured as described previously. 18 Ramos, OCI-LY1, OCI-LY3, OCI-LY7 and DHL-16 were gifts from Dr. Wing C. Chan (University of Nebraska, NE, USA) and were cultured in 10% fetal bovine serum lymphocyte medium.…”
Section: Methodsmentioning
confidence: 99%
“…Student T test (two samples with equal variance and two tailed) or Fisher’s exact test (2×2 table, two sided) for statistical significance was applied to compare mutation frequency between different regions or backgrounds. Semi-quantitative RT-PCR was performed as described previously (27, 29). Unstimulated B cells were obtained from naïve unimmunized mice that carry either VB1-8 or V-cSµ KI allele or both.…”
Section: Methodsmentioning
confidence: 99%
“…Unstimulated B cells were obtained from naïve unimmunized mice that carry either VB1-8 or V-cSµ KI allele or both. To avoid the survival or selection issue conferred by antigen, naïve splenic B cells were stimulated with anti-CD40/IL4 for 4 days as described previously (29), which induces B cell proliferation and survival independent of BCR engagement. Total RNA was purified with TriPure (Roche) and used for RT reaction according to manufacturer’s instructions (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Further study revealed that imbalanced PTEN and PI3K signaling impaired the μHC recombination in pro-B cells in Pten fl/fl mb1-Cre mice ( 12 ). Recently, emerging efforts have been placed to investigate the molecular mechanism of PTEN- and PI3K-tuned AKT signaling in regulating the strength of GC responses ( 14 , 15 , 23 ). B cell specific deficiency of PTEN in Pten fl/fl mb1 Cre/+ mice leads to the severe defects of B cell development at the bone marrow stage due to failed VJD recombination ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of the mature naïve B cell population in Pten fl/fl mb1 Cre/+ mice prevented the assessment of the function of PTEN in GCB-mediated CSR and antibody responses. As a solution, PTEN was recently knocked out in mature B cells in Pten fl/fl hCD20Tam Cre/+ mice, which demonstrated the importance of PTEN in regulating GC responses ( 23 ). Although mature B cell specific deficiency of PTEN in Pten fl/fl hCD20Tam Cre/+ mice excluded the B developmental defects as in the case of Pten fl/fl mb1 Cre/+ mice, the usage of Pten fl/fl hCD20Tam Cre/+ mice cannot explicitly separates the function of PTEN in mature B cell activation and proliferation upon antigen stimulation versus that in GC responses since GCBs were differentiated from activated mature naïve B cells after antigen stimulation.…”
Section: Introductionmentioning
confidence: 99%